The Effectiveness of Breast Care on Increasing Breast Milk Production in Mrs. N Post Sectio Caesarea in the Mawar Room of Kardinah Regional General Hospital, Tegal City - Rohanifah; Wahyuni Romadhon, Lily; Setyo Dwi Andhini, Citra (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Breast milk is an important component that needs to be considered, especially in terms of production and flow, as it has various benefits for the growth and development of infants. Mothers who have undergone a cesarean section often experience problems with breastfeeding due to inadequate breast milk production. Breastfeeding challenges in postpartum cesarean section mothers are caused by a decrease in oxytocin and prolactin hormones, which play a role in the smooth production of breast milk. To facilitate breast milk production, non-pharmacological efforts are needed, such as Breast Care. Breast Care is an effort to maintain the condition of a breastfeeding mother's breasts, both during pregnancy and after childbirth (postpartum period). Method: A descriptive method was used with the application of case study results. Result: The application of Breast Care conducted on January 2–4, 2025, to a post-cesarean section patient with breastfeeding issues was ineffective in the Mawar Room of Kardinah General Hospital in Tegal City. On the third day of the study, breast milk flow improved from a scale of 5 to a scale of 2, showing a significant increase. Conclusion: It can be concluded that the Breast Care technique is effective in increasing breast milk production in post-cesarean section patients in the Mawar Ward of Kardinah General Hospital in Tegal City.